Is nicotine vaporization a better alternative to traditional cigarette smoking? E-cigarettes harmful effects summary and the management of EVALI based on the latest literature - Szawica, Dominik; Kuźniar, Aleksandra; Fularska, Kamila; Oleszko, Michał; Wąsiewicz, Edward; Bernacki, Radosław; Bernacki, Piotr; Dutka, Martyna; Zardzewiały, Witold (Quality in Sport, 2023)
Introduction: Electronic cigarettes are battery-powered devices that allow users to inhale vapor produced by heating a liquid (e-liquid) containing nicotine and other substances. The first such devices were introduced in China in 2003, and subsequently approved for use in the European Union in 2006 and the United States in 2007. The number of e-cigarette users is constantly growing, with the largest increases observed in the 18-24 age group. Various modifications led to the emergence of a new disease entity in 2019 called EVALI (e-cigarette or vaping product use-associated lung injury). Aim of the study: To summarize the current state of knowledge about harmful substances contained in e-cigarettes and to systematize the latest methods of management in cases of suspected EVALI. Methods and materials: A literature review was conducted using PubMed, Google Scholar, and ScienceDirect, including publications from the last 8 years, using the following keywords: "E-cigarette," "Electronic cigarette," "EVALI," "THC," "Vitamin E." Results: Electronic cigarettes contain a number of substances harmful to health. E-cigarettes have not been approved as nicotine replacement therapy. The presence of vitamin E breakdown products in the respiratory tract of EVALI patients has been confirmed. Vitamin E was primarily used to increase the volume of e-liquids containing THC. Conclusions: Electronic cigarettes should not be used due to the numerous harmful substances they contain. When using e-cigarettes, both the devices and the e-liquids should be purchased from reputable sellers approved in the respective country. EVALI is a potentially fatal disease, and prompt diagnosis facilitates treatment